High Performance Polarization Beam Splitter Based on Cascaded Directional Couplers Assisted by Effectively Anisotropic Structures - Kaixuan Chen (IEEE Photonics Journal, 2019)
A high performance polarization beam splitter (PBS) based on cascaded directional couplers (DCs) assisted by effectively anisotropic structures is proposed. The sub-wavelength grating (SWG) structures between the two coupled waveguides act as anisotropic metamaterial cladding to block/enhance light coupling for transverse electric (TE)/magnetic (TM) polarization. Cascading the DCs designed at different central wavelengths can improve the extinction ratio (ER) within the desired bandwidth or broaden the working wavelength bandwidth for TM polarization. Three design examples show the excellent performance of PBS with ER of >35 dB, 20 dB or 14 dB and loss of <; 0.12 dB, 0.4 dB or 0.8 dB over a bandwidth (BW) of 60 nm, 250 nm or 400 nm, which is difficult to achieve in any PBS structure reported before. The BWER>20dB of the PBS based on the cascaded DCs increases by ~11 times when compared with a single DC.